Real-Time Sliding Mode and Moving Sliding Mode Control of 3-DOF Linear Parallel Robot - Aydin, Muhammet (Mdpi, 2025)
In this study, the design stages of a parallel robot with 3-DOF and linear motion are presented in detail. The position control of the linear robot, which was manufactured after the design process, was achieved in real time by using the inverse kinematic equations of the robot with the SMC method and the MSMC method. The highlights of the study are that the linear robot designed for a specific purpose has a unique design and the control of a 3-DOF linear robot with a MSMC method, which has not been found so far in the literature. In order to realize real-time position control, real-time SMC is implemented in the Matlab/Simulink R2017b environment. In addition, to increase the success of the SMC, the position control of the robot was also realized by a different method of moving the sliding surface. Humusoft MF634 card is compatible with Matlab and was used to transfer data in real time. Considering the point where the robot will be fixed, control was provided for the third region of the x-y cartesian coordinate system for position control. According to the results, the robot reached the desired reference values faster in the MSMC, with a difference of approximately 2 s. The robot reached the targeted values in 9.492 s with a maximum error of 0.06%, showing the effectiveness of the control mechanism. Considering the large size of the robot limbs, this result is satisfactory.
Keywords: real-time control; linear parallel robot; linear delta; position control; sliding mode control; moving sliding mode control